Pemberdayaan Siswa SMAN 1 Cimarga Melalui Produksi Konten Edukatif Di Youtube - Aisyah, Siti; Wardhana, Tulus Hendra; Octory, Gadis; Romaria, Gustina (Politeknik Penerbangan Indonesia Curug, 2025)
This community service program aims to enhance digital literacy and content creation skills among students of SMAN 1 Cimarga, Lebak, Banten, through the production of educational videos on the YouTube platform. The initiative addresses the limited use of digital media as an educational tool within the school environment. Conducted offline in April 2025, the program involved lecturers and students from Universitas Mercu Buana using a participatory and experiential learning approach. The training covered scripting, basic videography, video editing, and content distribution via the school’s YouTube channel. The results indicated a significant improvement in students' understanding of content production and increased confidence in expressing educational messages through digital media. Tangible outcomes included published educational videos, digital training modules, and a scientific article for dissemination. Collaboration with the school and support from the local education office contributed to the program's success. This initiative demonstrates that YouTube-based educational content creation can be an effective strategy to empower students as digital content creators with educational purpose.